Coronavirus Disease 2019 (COVID-19) in Neonates and Children From China: A Review - Yu, Yuanqiang; Chen, Pingyang (Frontiers in Pediatrics, 2020)
At the end of 2019, a novel coronavirus has spread in Wuhan, Hubei Province, China. The confirmed cases increased nationwide rapidly, with increased population mobility during Chinese Lunar New Year festival. The World Health Organization (WHO) subsequently named the novel coronavirus pneumonia Coronavirus Disease 2019 (COVID-19) and named the virus Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Soon, transmission from person to person was confirmed and the virus spread to many other countries. To date, many cases have been reported in the pediatric age group, most of which were from China. The management and treatment strategy have also been improved, which we believe would be helpful to pediatric series in other countries as well. However, the characteristics of neonatal and childhood infection still have not been evaluated in detail. This review summarizes the current understanding of SARS-CoV-2 infection in neonates and children from January 24 to May 1, as an experience from China.